ARTISTIC INTERPRETATION OF THE NOVEL “MUVOZANAT” BY ULUGBEK HAMDAM (American Journal of Technology and Applied Sciences, 2024)
In this article, the famous writer and literary scholar Ulug'bek Hamdam talks about the characters of the work “Muvozanat”, their fate, keeping the material world and the spiritual world in the same balance, and the problems of a person not going beyond his own, not deviating from the path of a clear goal. z is maintained.